2023
DOI: 10.3390/jfb14100521
|View full text |Cite
|
Sign up to set email alerts
|

Selective Laser Melting and Spark Plasma Sintering: A Perspective on Functional Biomaterials

Ramin Rahmani,
Sérgio Ivan Lopes,
Konda Gokuldoss Prashanth

Abstract: Achieving lightweight, high-strength, and biocompatible composites is a crucial objective in the field of tissue engineering. Intricate porous metallic structures, such as lattices, scaffolds, or triply periodic minimal surfaces (TPMSs), created via the selective laser melting (SLM) technique, are utilized as load-bearing matrices for filled ceramics. The primary metal alloys in this category are titanium-based Ti6Al4V and iron-based 316L, which can have either a uniform cell or a gradient structure. Well-know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 191 publications
0
2
0
Order By: Relevance
“…A cranial-maxillofacial implant was fabricated using SLM-SPS technology by Rahmani et al, as shown in Figure 8g. The integration of SLM and SPS technologies signifies a robust and state-of-the-art method in the realm of cranio-maxillofacial implant fabrication [166]. This novel strategy utilizes the advantages of both techniques to develop customized, highly efficient, and visually appealing implants.…”
Section: Biomedical Implantsmentioning
confidence: 99%
“…A cranial-maxillofacial implant was fabricated using SLM-SPS technology by Rahmani et al, as shown in Figure 8g. The integration of SLM and SPS technologies signifies a robust and state-of-the-art method in the realm of cranio-maxillofacial implant fabrication [166]. This novel strategy utilizes the advantages of both techniques to develop customized, highly efficient, and visually appealing implants.…”
Section: Biomedical Implantsmentioning
confidence: 99%
“…Design freedom for complex geometries-MAM offers unparalleled design freedom in situ. Engineers can create intricate, lightweight, and optimized structures that were previously impossible or too costly to produce using conventional methods [26]. The technology enables the production of complex geometries that precisely match the workpiece, Allied automation-This solution prepares allied automation principles to optimize the internal logistics process.…”
Section: Intralogistics Approachmentioning
confidence: 99%
“…During immersion tests in artificial saliva and simulated body fluid solutions, coatings containing multi-walled carbon nanotubes demonstrated excellent bioactivity [66]. Furthermore, sbioactive Ti-based biomedical composite materials were developed by combining traditional biomedical alloys with biomedical ceramics (such as titanium dioxide, zirconium dioxide, hydroxyapatite, or tricalcium phosphate) [67]. Berger et al conducted surface modification on Ti-Nb-Zr-Hf-Ta HEA to render its surface bioactive [68].…”
Section: Enhancing Biocompatibilitymentioning
confidence: 99%